Multiplication of Musa acuminata C. Planlets with the Addition of NAA and Coconut Water In-vitro - Muhammad Zakky Mubarak; Ratnasari, Evie (LenteraBio : Berkala Ilmiah Biologi, 2024)
The main issue of production Mas Kirana's bananas (Musa acuminata C.) is limited seeds. The utilization of NAA (Naphthalene Acetic Acid) and coconut water can be used to support the success of multiplication in tissue culture in vitro. The purpose of this study was to determine the effect of adding NAA and coconut water and their concentrations on the multiplication of Mas Kirana banana plantlets in vitro. This experimental study used a completely randomized design (CRD) with one treatment factor, namely a combination of NAA and coconut water concentrations including (0 mg/L NAA + 0% Coconut water, 1 mg/L NAA + 10% Coconut water, 2 mg/L NAA + 15 % coconut water, 3 mg/L NAA + 20 % coconut water, 4 mg/L NAA + 25 % coconut water). Results showed that the addition of NAA and coconut water affected multiplication of Mas Kirana banana plantlets, most optimally with C treatment (3 mg/L NAA + 20% Coconut Water) for all parameters, including number of shoots with an average of 2.00, number of leaves 5.20, and number of roots 6.20 and plantlet height with an average of 2.48 cm.